Understanding parenting patterns and their influence on the nutritional status of stunted toddlers: A phenomenological study - Laila, Jelita Nur; Astuti, Tyas Puji; Aziza, Fitri Anaaan Nur; Vikri, Muhammad (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Stunting in toddlers remains a critical public health concern in Indonesia due to its long-term effects on child development, quality of life, and national human capital. It is not merely a result of chronic undernutrition, but also deeply influenced by parental care patterns—especially those of mothers socioeconomic conditions, nutritional literacy, time constraints, and engagement with primary health services such as posyandu and community clinics. Despite multiple government interventions, stunting rates remain high, highlighting a gap between policy frameworks and ground realities. Methods: This study employs a qualitative phenomenological approach to explore how low-income mothers manage household food security, develop feeding strategies, and respond to the risk of stunting. Data were gathered through in-depth interviews, participatory observations, and focus group discussions (FGDs). Thematic analysis was conducted through transcription, data reduction, coding, and interpretive synthesis. Findings: Often shaped by children's activity levels rather than biomedical indicators. Community health interventions were found more effective when participatory and trust-based. The study identifies a significant gap between technocratic approaches focused on nutrition metrics and the contextual needs of mothers. Conclusion: Advocating for locally grounded, dialogic, and empowering interventions that strengthen emotional, social, and cultural capacities to sustain household nutritional resilience. Novelty/Originality of this article: The novelty/originality of this article lies in exploring mothers’ lived experiences managing stunting risk, revealing gaps between technocratic nutrition policies and the contextual, culturally grounded needs of low-income Indonesian families.